THE USE OF ALOE VERA GEL ON SCAR COLLAGEN - Nur Alam, Amania; Jailani, Muhammad; Hajar, Siti (Universitas Airlangga, 2019)
Highlights: The active chemical compounds present in Aloe vera are known to be efficacious in the process of healing open wounds. The use of Aloe vera can significantly improve scar collagen, with the highest improvement observed in the group treated with 50% Aloe vera gel. Abstract: Introduction: Aloe vera have active chemicals substances including saponins, tannins, flavonides, and polyphenols. Saponin takes a role as a disinfectant, so it is normally effective for healing any open wounds, while tannins have ability to be an antiseptic. This study aims to see how the effect of the Aloe vera gel on wound collagen, and too inspect which is the most effective concentration of the Aloe vera gel in the formation of wound collagen in wistar strains (Rattus novergicus) rats. Methods: This study uses a post-test only method with control group design. The subjects of this study were 28 male Wistar rats (Rattus novergicus). The subjects were divided into 4 groups consisting of 1 negative control group and 3 treated groups, the control group was not given any treatment, while the treated group was given the Aloe vera gel with each concentrations of 12.5%, 25%, and 50% respectively. The experiment was started by making a wound on the back of the rat which then be followed by applying the gel to the wound for 14 days. Results: The results showed the group with the 50% Aloe vera gel treatment had the best collagen formation, followed by a concentration of 25%, 12.5%, and the control group. Therefore, the used of Aloe vera has given good change in scar collagen, and the best scar collagen can be viewed in the group with 50% concentrate of Aloe vera. Conclusion: Increasing the concentration of applied Aloe vera gel led to the development of thicker collagen tissue in wounds on male white rats (Rattus novergicus strain Wistar). This suggests that Aloe vera may serve as a viable alternative treatment for wounds in our daily lives.